Gödel and the language of mathematics - Kostić Jovana (Belgrade Philosophical Annual, 2015)
The aim of this paper is to challenge Hao Wang's presentation of Gödel's views on the language of mathematics. Hao Wang claimed that the language of mathematics is for Gödel nothing but a sensory tool that helps humans to focus their attention on some abstract objects. According to an alternative interpretation presented here, Gödel believed that the language of mathematics has an important role in acquiring knowledge of the abstract mathematical world. One possible explanation of that role is proposed.